Trace elements as a diagnostic biomarker for premalignant lesions and malignant conditions - Surekha Rathod; Prachi Rathi; Vivek Harkare (SRM Journal of Research in Dental Sciences, 2019)
The aim of this paper was to study and compare the levels of copper (Cu), iron (Fe), and zinc (Zn) in patients with premalignant lesions or malignant conditions. A schematic search was conducted according to population, intervention, comparison, outcome in order to obtain appropriate articles for critical appraisal. The review incorporated a total of 16 articles, including in vivo human studies published in English language. Studies with premalignant and malignant conditions and trace elements including Cu as an essential element and Fe and Zn as other elements were considered. No limit was placed on a number of patients and studies involving blood investigations were included in this review. The exclusion criteria were in vitro nonhuman non-English studies. Case series, case reports, retrospective studies, and studies involving only saliva/tissue investigations were also excluded and studies not having any of the above-mentioned trace elements were also excluded from the study. Results of the studies suggested that serum Cu and Zn as well as the Cu to Zn ratio can be used as biomarkers for oral precancer and cancer. Thus, a comprehensive understanding of these trace elements can be used as a reliable biomarker for development and progression of oral cancer.